A scalable and facile process for the preparation of N-(pyridin-4-yl) piperazine-1-carboxamide hydrochloride. (1st March 2016) - Wei, Daiyan; Chen, Ligong; Yan, Xilong; Li, Yang; Li, Jianye; Wang, Donghua
A scalable and facile synthetic process for N-(pyridin-4-yl)piperazine-1-carboxamide hydrochloride, a novel Rho kinase inhibitor with an unsymmetrical urea structure currently under investigation for the treatment of central nervous system disorders, was established. After optimisation of the reaction conditions, N-(pyridin-4-yl)piperazine-1-carboxamide hydrochloride was synthesised from 4-aminopyridine and N, N'-carbonyldiimidazole through acylation, deprotection and salt formation. This new procedure affords the product in 53% overall yield with high purity and it can be easily scaled up for production.